Hubungan Kepatuhan Konsumsi Tablet Zat Besi dengan Kejadian Anemia Ibu Hamil - Ginanjar Zukhruf Saputri; Ana Hidayati; Susan Fitria Candradewi; Sulfah Sulfah (Journal Syifa Sciences and Clinical Research, 2022)
Anemic in Pregnancy is still a health problem in Indonesia. Iron supplementation is a preventive measure carried out by the government in primary health services. However, the average coverage of national Fe tablets is still not maximal (85.1%). Research related to adherence to iron supplement consumption is still limited, therefore this study aims to determine the relationship between adherence level with anemia of pregnant women. The study used an analytic observational method with a cross sectional approach, conducted in the period August-November 2019 at Jetis I Bantul, primary health service Yogyakarta. A total of 39 respondents who met the inclusion criteria and agreed to informed consent were recruited in this study. Data on the level of compliance were taken through interviewing respondents using quistionnaire and pill count, at least on the 7th day after consuming iron tablets, while Hb levels were taken from medical records and examination of respondents. Statistical analysis was performed using chi square. Results showed that 61.5% of pregnant women complied with the consumption of iron tablets, while the measurement of the pill count showed 59.0% has complience. There was a significant correlation between the consumption of iron tablets and the incidence of pregnancy anemia, both adherence to the questionnaire measurement p = 0.000; OR = 0.050; (CI: 0.010-0.263), or the measurement of pill count p = 0.003; OR = 0.126 (CI: 0.030-0.538). A total of 15.4% of pregnant women have anemia in the 2nd trimester of gestation, and 25.6% in the 3rd trimester. Based on this study, it is concluded that there is a correlation between the level of adherence  of  Iron tablet consumption towards the incidence of anemia in pregnant women.